Effects of selective and non-selective beta-adrenergic blockade on coronary dynamics in man assessed by rapid atrial pacing. Issue 8 (August 1978) - Stephens, J; Hayward, R; Ead, H; Adams, L; Hamer, J; Spurrell, R
Abstract : The effects on coronary dynamics of propranolol and atenolol were studied in 12 patients undergoing cardiac catheterisation for suspected coronary artery disease. Myocardial blood flow was measured using the coronary sinus continuous thermodilution technique. Data were obtained immediately after drug administration and during rapid atrial pacing. The immediate effects were similar for both drugs. A significant reduction in heart rate was accompanied by a small reduction in myocardial oxygen consumption. Changes in coronary sinus flow induced by rapid pacing were closely related to changes in tension-time index. This relation was not modified by propranolol or atenolol. Neither propranolol nor atenolol therefore has significant coronary vasoconstrictor properties. Cardioselectivity appears to be unimportant with respect to beta-adrenergic blockade and the coronary circulation.